Amyand hernia: an incidental finding and literature review - Roberto de Y. Botello-Arredondo; Yannin Mesa-Báez; Noé A. Valderrama-Cervantes (Revista Médica del Hospital General de México)
Amyand hernia (AH) is an uncommon pathology occurring in any age range. The symptoms are those of a complicated or uncomplicated inguinal hernia. Diagnosis is intraoperative and may be accompanied by ultrasound and computed tomography. A 56-year-old male presented to the clinic for right inguinal hernia. He underwent right inguinal plasty and a vermiform appendix was found within the contents of the hernia sac. AH with appendicitis or without appendicitis is often a rare incidental finding, so its treatment is not well established and is a challenging decision for the surgeon.